2002
DOI: 10.1046/j.1365-2796.2002.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipids, lipoprotein(a) level, and apolipoprotein(a) isoforms as prognostic markers in patients with coronary heart disease

Abstract: Abstract. Lundstam ULF, Herlitz J, Karlsson T, Linde Ân T, Wiklund O (Sahlgrenska University Hospital, Go Èteborg University, Go Èteborg; Sweden) Serum lipids, lipoprotein(a) level, and apolipoprotein(a) isoforms as prognostic markers in patients with coronary heart disease. J Intern Med 2002; 251: 111±118.Objective. Our objective was to study prognostic factors for death in patients with coronary heart disease (CHD), focusing on serum lipids and lipoproteins. Design and subjects. The study subjects were 964 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
(63 reference statements)
2
21
0
Order By: Relevance
“…This is in accordance with data from the ECAT and other trials [40,[43][44][45][46][47]. However, other studies showed partly conflicting results [41,[48][49][50][51]. Our data support the concept that CAD risk management cannot simplified to LDL-C reduction [52].…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with data from the ECAT and other trials [40,[43][44][45][46][47]. However, other studies showed partly conflicting results [41,[48][49][50][51]. Our data support the concept that CAD risk management cannot simplified to LDL-C reduction [52].…”
Section: Discussionsupporting
confidence: 91%
“…However, for early stages of atherosclerosis, Lp(a) concentrations but not apo(a) isoforms were found to be predictive (4 ). Using multiple regression analysis, some studies found that apo(a) size was more important than Lp(a) concentrations (13 ), whereas others found that only Lp(a) concentrations were predictive (3, 11, 14 -18 ). We found that small apo(a) size is an independent predictor of angina regardless of Lp(a) concentration and that no additivity or synergism was present.…”
Section: Discussionmentioning
confidence: 99%
“…However, discordant results have been reported concerning the contribution of apo(a) size to CHD risk independent of Lp(a) concentrations (3,4,(11)(12)(13)(14)(15)(16)(17)(18). Substantial methodologic variation in determining Lp(a) concentrations and apo(a) size may explain the difference in findings.…”
mentioning
confidence: 94%
“…Previous studies have examined the role of apo(a) isoform size on CHD prediction (24)(25)(26)(27)(28)(29)(30), and some of these studies have attempted to separate the prediction relative to isoform size from that of plasma levels of Lp(a). In a small case-control study, Kraft et al ( 26 ) have reported that both Lp(a) levels and isoform size were associated with CHD, but when both variables were entered in the multivariate model, the strength of the association was higher for apo(a) isoform size.…”
Section: Discussionmentioning
confidence: 99%